Mammalian African trypanosome VSG coat enhances tsetse’s vector competence - Aksoy, Emre (Proc Natl Acad Sci U S A, 2016)
Tsetse flies are biological vectors of African trypanosomes, the protozoan parasites responsible for causing human and animal trypanosomiases across sub-Saharan Africa. Currently, no vaccines are available for disease prevention due to antigenic variation of the Variant Surface Glycoproteins (VSG) that coat parasites while they reside within mammalian hosts. As a result, interference with parasite development in the tsetse vector is being explored to reduce disease transmission. A major bottleneck to infection occurs as parasites attempt to colonize tsetse’s midgut. One critical factor influencing this bottleneck is the fly’s peritrophic matrix (PM), a semipermeable, chitinous barrier that lines the midgut. The mechanisms that enable trypanosomes to cross this barrier are currently unknown. Here, we determined that as parasites enter the tsetse’s gut, VSG molecules released from trypanosomes are internalized by cells of the cardia—the tissue responsible for producing the PM. VSG internalization results in decreased expression of a tsetse microRNA (mir-275) and interferes with the Wnt-signaling pathway and the Iroquois/IRX transcription factor family. This interference reduces the function of the PM barrier and promotes parasite colonization of the gut early in the infection process. Manipulation of the insect midgut homeostasis by the mammalian parasite coat proteins is a novel function and indicates that VSG serves a dual role in trypanosome biology—that of facilitating transmission through its mammalian host and insect vector. We detail critical steps in the course of trypanosome infection establishment that can serve as novel targets to reduce the tsetse’s vector competence and disease transmission.